Guest

if x/b+c-a=y/c+a-b=z/a+b-c. show that x^3(b-c)^3+y^3(c-a)^3+z^3(a-b)^3=3xyz(a-b)(b-c)(c-a)

if x/b+c-a=y/c+a-b=z/a+b-c.
show that x^3(b-c)^3+y^3(c-a)^3+z^3(a-b)^3=3xyz(a-b)(b-c)(c-a)

Grade:

1 Answers

Saurabh Koranglekar
askIITians Faculty 10336 Points
2 years ago
Dear student

Please write the Question in a standard form or attach an image of the question

Regards

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free